Comparing the efficacy of a novel mucoadhesive patch containing Nigella sativa 10% with triamcinolone 0.1% in patients with erosive‐atrophic oral lichen planus: A pilot study - Atessa Pakfetrat; Zahra Delavarian; Mahshid Malakooti; Hossein Bagheri; Habibollah Esmaily; Mahsa Ghorbani; Pooya Saeedi (Wiley, 2024)
Abstract Objective This study evaluates the efficacy of a novel mucoadhesive patch containing Nigella sativa 10% extract compared to triamcinolone 0.1% in alleviating symptoms and reducing lesion severity in patients with erosive‐atrophic oral lichen planus. Methods and Materials A pilot study comprising two groups, each with 10 patients, was conducted. The intervention group received mucoadhesive patches containing N. sativa 10% extract, while the control group received triamcinolone acetonide 0.1% patches. Pain and burning intensity, measured through visual analog scale, and lesion severity based on the Thongprasom scale were assessed weekly for 4 weeks. Descriptive records were kept for side effects and patient satisfaction. Results Pain and burning intensity decreased in both groups throughout the sessions, with the N. sativa group showing a greater reduction than the triamcinolone group. The reduction in burning intensity within each group was significant (p < .001), and there was a significant difference between groups only in the second session (p = .045). The overall difference between groups was not significant (p > .05). Lesion severity also decreased significantly in both groups (p < .001), with a significant difference between groups observed in the third session (p = .043) and overall throughout the study (p = .006). Conclusion The use of N. sativa extract in mucoadhesive patches was as effective as corticosteroids in reducing pain, burning, and lesion severity in patients with oral lichen planus, with N. sativa showing superior results in some sessions. Notably, no significant complications were observed with N. sativa use, making it a promising treatment option for lichen planus.